The Testing of Several Formulations of Vetiver (Vetiver zizanioides) On the Mortality of Rice Weevils (Sitophilus oryzae) (International Forum of Researchers and Lecturers, 2025)
Rice stored in households often does not meet good agricultural product storage standards. Problems arise when products are stored in unsuitable containers, making them more susceptible to insect infestation. Pest insects that cause damage to the quality and quantity of rice can easily reduce rice quality. The use of synthetic chemical insecticides is inappropriate for post-harvest products, as these products are consumed shortly after storage. One environmentally friendly and non-toxic option for consumers is the use of plant-based materials known as biopesticides derived from plant sources. The objective of this study was to determine the mortality rate of rice weevils treated with several formulations of vetiver root (Vetiver zizanioides), both individually and in combination. The study was conducted at the Integrated Laboratory of Polytechnic of Banjarnegara. A total of 20 adult rice weevils from breeding were infested in jars containing 100 g of rice. The study used a completely randomized design with 7 treatments: A0: control; A1: 15 g of vetiver root powder; A2: 0,05 mL of vetiver root oil; A3: 15 g of vetiver root extract; A4: fragrant root powder 7,5 g and fragrant root extract 7,5 g; A5: fragrant root powder 7,5 g and fragrant root extract 7,5 g; A6: fragrant root powder 7,5 g and fragrant root oil 0,05 mL. Each treatment used 4 replicates, resulting in 28 experimental units. The parameters observed were the percentage of rice powder, percentage of weight loss, percentage of rice with holes, and percentage of rice weevil mortality. Observations were conducted at one-week intervals. The data obtained for each parameter were analyzed using an F-test, and if significant differences were found, a Duncan test was conducted at the 5% level. Observations of rice weevil mortality were conducted at 1 week after treatment (1 wat) and 2 wat.